Pengaruh Media ARTIME FUN(ART TIME FUN) terhadap Hasil Belajar Siswa Kelas 2 Materi Durasi Waktu - Paramita, Diah Ratri; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of learning innovation is that the author hopes that innovations such as the ARTIME FUN media given to students can improve their understanding of the material by looking at the improvement in their learning outcomes. This research was conducted at SD N Podorejo 3 with the research objects being class II students. This research was conducted using qualitative research methods through interviews, observation, documentation, pre-test and post-test for evaluation. The results of the pretest and posttest carried out before the learning media were provided were classified as low. The results after being given the ARTIME FUN learning media showed that the results of the pretest and posttest that had been carried out by the students had increased. This means that class II students after being given interesting learning media can improve their understanding of learning material so that they can improve their learning outcomes. The average pretest score was 50% and the posttest reached 65.9% with a percentage increase of 15.9%. Based on the results above, it can be concluded that ARTIME FUN learning media can improve student learning outcomes.